Does iQOS harvest personal data from users and manipulate their tobacco habits?: A review of current evidence - Krzysztof Przewozniak; Silvano Gallus; Paweł Koczkodaj (Tobacco Induced Diseases, 2019)
Objective To review available reports on harvesting personal data about tobacco habits from iQOS users and raise awareness of tobacco users and tobacco control community on this risk.